Best practices to prevent out of sequence construction activities - Nurul Izati, Shahidan (2019)
Delays in the construction industry are not something alienated anymore. The common problems and challenges in construction project are delay in implementation and operation. One of the causes of construction delays are out of sequence construction activities. Therefore, this study is conducted to identify the feasible practices to prevent out of sequence in construction projects. The research method that is being used in this study is individual interviews with industry practitioners from the construction industry. The findings of this study have shown that the most highlighted practices to prevent out of sequence construction activities lie upon the upper management and lower management that involves in the construction project itself.